FORMULA ESTABLISHMENT OF COLORLESS Pb(II) COMPLEX WITH N-BENZOYL-N-PHENYL HYDROXYLAMINE (BPA) USING ATOMIC ABSORPTION SPECTROSCOPY - Dhananjay B Sarode; Sopan T Ingle; Sanjay B Attarde (Universitas Gadjah Mada, 2012)
A new method for determination of stoichiometry of colorless complexes by using atomic absorption spectrophotometric technique in continuous variation method and slope ratio method was described here. This method can be used in same manner as that of mole ratio method and slope ratio method. In this method atomic absorption spectroscopy was used instead of UV-Vis spectrophotometry. Atomic absorption spectrophotometric technique is superior to UV-Vis spectrophotometry as it can be applied to colorless soluble complexes. Pb(II) and n-benzoyl-n-phenyl hydroxylamine react to form colorless complex at pH 6.5, which can be easily determined by this method. It was found that Pb(II) forms 1:2 complex with n-benzoyl-n-phenyl hydroxylamine and is quantitatively extracted back to aqueous solution for AAS analysis.